Genome Sequence of a Persistent Campylobacter jejuni Strain, 2016-IZSVE-19-111250 - Peruzzo, Arianna (Microbiol Resour Announc, 2020)
In this report, we present the whole-genome sequence of a Campylobacter jejuni strain isolated recursively for the last 3 years from an Italian poultry farm.